Associations Between Daytime Sleepiness, Psychological Symptoms, Headache, and Abdominal Pain in Schoolchildren - Gustafsson ML; Laaksonen C; Salanterä S; Löyttyniemi E; Aromaa M (United States, 2022)
Daytime sleepiness and different symptoms are common problems affecting health and well-being of schoolchildren. This population-based cohort study included 568 children who were followed from ages 10 to 15 years. Daytime sleepiness, headache, abdominal pain, and psychological symptoms (depression, irritability or bad temper, nervousness, anxiety, and dejection) were assessed by self-administered questionnaires. The prevalence of frequent daytime sleepiness was 13% at the ages of 10 and 12 years and increased significantly up to 24% at the age of 15 (p < .0001). Daytime sleepiness as well as psychological symptoms were positively associated with headache and abdominal pain from ages 10 to 15 years. Headache in girls at the ages of 10 predicted the occurrence of headache at the age of 15. School nurses and other professionals need to understand the importance of a holistic evaluation of sleep and different symptoms in children. There is also a need for interventions targeting several co-occurring symptoms.